Sodium ion storage performance of magnetron sputtered WO3 thin films. (20th October 2019) - García-García, Francisco José; Mosa, Jadra; González-Elipe, Agustín R.; Aparicio, Mario
Abstract: WO3 thin film electrodes were successfully prepared by magnetron sputtering (MS) deposition under an oblique angle configuration (OAD). Intercalation of Na ions in the tungsten oxide layers has been studied using electrochemical techniques. Sample characterization before and after sodium intercalation has been carried out by Raman, XPS and XRD measurements. ToF-SIMS analysis has been also performed in order to analyze the element depth profiles along the electrode thickness. Electron microscopy evaluation of the cross section confirms the porous structure of the coatings. Batteries integrating these WO3 electrodes have a discharge capacity of 120 mA h g −1 at the initial cycles and show an adequate capacity retention upon 300 cycles. The WO3 -OAD thin-films are proposed as promising electrodes for Na-ion batteries. Highlights: WO3 thin film electrodes were successfully prepared by magnetron sputtering under an OAD. Intercalation of Na + in WO3 layers has been shown by XRD, Raman XPS and TOF-SIMS. SEM evaluation of the cross-section confirms the coatings porous structure. WO3 electrodes show a discharge capacity of 120 mA h g −1 at the initial cycles. WO3 MS-OAD thin films are promising anode candidate towards enhanced Na storage.